2009
DOI: 10.1088/0957-4484/20/47/475606
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymeric nanocomposites and porous materials prepared using organogels

Abstract: We propose a new method for preparing polymeric nanocomposites and porous materials using self-assembled templates formed by 1,3:2,4-dibenzylidene sorbitol (DBS) organogels. DBS is capable of self-assembling into a 3D nanofibrillar network at relatively low concentrations in some organic solvents to produce organogels. In this study, we induced the formation of such physical cross-linked networks in styrene. Subsequently, we polymerized the styrene in the presence of chemical cross-linkers, divinyl benzene (DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In our earlier studies, 12 DBS organogels were used as selfassembled scaffolds for preparing polystyrene (PS) nanocomposites and porous materials. DBS molecules were dissolved in styrene/initiator mixtures at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, 12 DBS organogels were used as selfassembled scaffolds for preparing polystyrene (PS) nanocomposites and porous materials. DBS molecules were dissolved in styrene/initiator mixtures at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1,3:2,4-Di-O-benzylidene-D-sorbitol (DBS) and its methylsubstituted derivatives, 1,3:2,4-di-O-p-methylbenzylidene-D-sorbitol (MDBS) and 1,3:2,4-di-O-m,p-dimethylbenzylidene-D-sorbitol (DMDBS) as shown in Scheme 1, are commercially available chiral amphiphilic polyols with a buttery shaped structure, and have been widely used as nucleating agents in polymers, such as poly(ethylene terephthalate), 23 polypropylene [24][25][26] and poly(L-lactic acid), 27 and the self-assembled nanobrils also act as reinforcing agents to improve the mechanical properties of polymers, such as epoxy and polystyrene. 28,29 Later, they were found to be versatile gelators for a wide range of low molecular mass organic liquids due to their chirality and hydrogen bonding. [30][31][32][33][34][35][36] Janssen et al 6 rst used DBS to gel an LC host, and reported the electrically controlled light scattering characteristics of the LC physical gel lm, but the driving voltage was high, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…DBS gels could provide commercial and technological benefits for electrolytes, cosmetics, and so on. , Recently, DBS gels have been used as templates to synthesize porous polymers such as polystyrene (PS). Moreover, because of the presence of nanofibrillar networks, these gels can act as reinforcing materials to enhance the thermal and mechanical properties of PS …”
Section: Introductionmentioning
confidence: 99%